Kompensasi Ngayah Secara Finansial di Desa Adat Ulakan, Kecamatan manggis, Kabupaten Karangasem - Dwi Pratiwi, Ni Kadek Indah; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
One of the cultural traditions in Bali that has been passed down through generations is ngayah. When the community customary wander village ulakan go, they would have obstacles taking the time to ngayah worn so they choose mogpog or dedosan. This research was conducted to analyze how the social influence of ngayah compensation with some money termed as mogpog or dedosan in Ulakan Traditional Village.The theory chosen as a scalpel in this study was Georg Simmel's Money Sociology. It is not always that social obligation ngayah which can be replaced with money where it will be able to provide a sense of relief and freedom for those who wander or migrant permanent and impermanently. Social actions such as tolerance, mutual understanding, and kinship that still exist in Ulakan Traditional Village is a good communal manners, therefore, it is good to be maintained. Keywords: Ngayah, compensation, migrating, social obligation